Connection Habit Snacks and Consumption Food with the Nutritional Status of Children at Elementary School Inpres 08 Mamboro - Siti Khopipah AR. Kilat; Budiman; Eka Prasetia Hati Baculu (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
School-age children play a strategic role as an investment for the nation's progress, considering they are the future generation. Optimal growth and development in school-age children heavily rely on the provision of nutrition and nutrient intake. Snacking habits and food consumption play a crucial role in determining children's nutritional status, as imbalanced food intake can lead to nutritional problems such as malnutrition or obesity. This study aims to investigate the relationship between snacking habits and food consumption with children's nutritional status.This research employs a quantitative approach with a cross-sectional research design. The population in this study consists of sixth-grade students at Elementary School Inpres 08 Mamboro with a sample size of 48 respondents. Data were collected using a questionnaire covering variables such as snacking habits, food consumption, and children's nutritional status. Analysis indicates that the majority of respondents have poor snacking habits (64.6%) and inadequate food consumption (58.3%). Chi-square test results demonstrate a significant relationship between snacking habits and children's nutritional status (? = 0.004) and between food consumption and children's nutritional status at Elementary School Inpres 08 Mamboro (? = 0.00). Poor snacking habits and food consumption can negatively impact children's nutritional status, while good food consumption can help maintain optimal nutritional status. Therefore, efforts are needed to enhance understanding and practice of healthy eating habits among school-age children to support their growth and development.